Interlocução entre a pré-escola e as tecnologias de informação e comunicação à luz da legislação - Costa, Carina Aparecida Bento da (2017)
This research is a study on preschool of regular education and the Information and Communication Technologies (ICTs), and it aims to investigate and synthesize the interlocution between preschool and the ICTs in the light of the current Brazilian legislation. The methodology used is a qualitative approach with bibliographic and documentary data. Official documents and bibliographic sources that guide Brazil’s regular preschool education were mapped, considering important references such as Kishimoto (2003; 2010) and Kuhlmann Júnior (2015). It has identified the profile of child, childhood, early childhood education and preschool in the federal documents and laws. Concurrently, a bibliographical research based on authors such as Kenski (2007) and Tapscott (2010) was carried out, pointing out the characteristics of ICTs and considering the new generations from the internet age who have arrived in schools. Subsequently, it followed the analysis and elaboration of charts with information about the main guiding documents of basic education, publications about children's education, Brazilian educational legislation and complementary sources to contribute with the object of this investigation. Five official documents (BRASIL, 1996; 2006b; 2009b; 2010; 2014b) were selected for a more detailed analysis from two categories of analysis: preschool and ICTs. The category preschool considered the verification of federal documents from the keyword ‘preschool’ and the ICT category analyzed the federal documents from the following keywords: ‘audiovisual’, ‘computer’, ‘digital’, ‘Internet’, ‘media’, ‘technologies and ICTs’, considering their correlative words. The results of the analyses of the Brazilian education federal documents pointed the current context of the TICs in the preschool, showing that the interlocution between both should be more evident from the point of view of the federal documents. In conclusion, there are many contributions of the interlocution between ICTs and preschool, and in contrast this study presents challenges to be faced in this stage of education due to federal documents that direct the education in the country and present little evidence of the relation of the TICs with the process of teaching-learning, then, it is necessary to carry out new researches in order to point out ways for teachers and schools to take advantage of the possibilities of these technological resources in preschool.